Granulomatous dermatosis: histopathological study in a tertiary care hospital - Srinivas, Teerthanath; S., Hariprasad (International Journal of Research in Medical Sciences, 2017)
Background: Granulomatous dermatosis shares the histological finding of granuloma formation; it is usually formed because of the persistence of a non-degradable product of active hypersensitivity. The identical histological picture may be produced by several causes, which pose a diagnostic challenge to dermatopathologist, Present study aims at classifying cutaneous granulomatous dermatosis based on the morphology and aetiology of granulomas, and to highlight its significance for specific clinical diagnosis. Methods: A retrospective analysis of skin biopsy was done and cases of cutaneous granulomatous lesions diagnosed on histopathological examination were retrieved for a period of 8 years. Clinical data and diagnosis were retrieved from hospital records. Hematoxylin and eosin stained paraffin sections were reviewed. The morphological pattern of granuloma was classified into sarcoidal, necrotizing, necrobiotic and suppurative granulomas and further aetiological evaluation for the granulomatous dermatosis were done using various special stains like Periodic Acid Schiff stain, Fite-Farraco stain, Gomori methenamine silver stain and acid-fast bacilli stain. Results: A total of 228 cases of cutaneous granulomatous lesion were retrieved; out of these 93cases (40.79%) were sarcoidal granuloma type, 83cases (36.40%) were of suppurative granulomas, 29 cases (12.72%) were of necrobiotic granulomas, 20 cases (8.77%) were necrotizing granuloma and 3 cases (1.32%) had granulomatous dermatitis with vasculitis. Infective aetiology was the commonest cause for granulomatous dermatosis (57.89%), mainly by leprosy, tuberculosis and various fungal infection. Conclusions: Granulomatous dermatosis has significant overlap in histopathological picture of various granulomatous reactions. Morphology alone is seldom specific and cannot be used as diagnostic tool. It is better understood based adequate clinical data, morphology of granuloma, special stains and laboratory workup in arriving at a etiology specific diagnosis for definitive clinical management.